Welfare, Modernity, and the Weimar State - Hong, Young-Sun (Book collections on Project MUSE., 2014)
This is the first comprehensive study of the turbulent relationship among state, society, and church in the making of the modern German welfare system during the Weimar Republic. Young-Sun Hong examines the competing conceptions of poverty, citizenship, family, and authority held by the state bureaucracy, socialists, bourgeois feminists, and the major religious and humanitarian welfare organizations. She shows how these conceptions reflected and generated bitter conflict in German society. And she argues that this conflict undermined parliamentary government within the welfare sector in a way.